2019
DOI: 10.1371/journal.pone.0216740
|View full text |Cite
|
Sign up to set email alerts
|

The disease spectrum of adult patients at a tertiary care center emergency department in Lebanon

Abstract: Objective There is an increase in Emergency Department (ED) utilization globally. Understanding what patients present to EDs with is important for resource allocation, training and staffing purposes. There is paucity of data pertaining to ED visit presentations in Lebanon. This study aims at describing the spectrum of diseases among adult patients who present to a tertiary care center in Lebanon, an upper-middle income country (UMIC). Methods A retrospective chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…On the other hand, Martin-Gill and Reiser found that mental health disorders were the most common initial visit diagnosis among HRURVs, which did not emerge in our study 8. In fact, in a study on disease spectrum of ED visits in Lebanon, mental health disorders were not among the diagnoses found in their sample 17…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, Martin-Gill and Reiser found that mental health disorders were the most common initial visit diagnosis among HRURVs, which did not emerge in our study 8. In fact, in a study on disease spectrum of ED visits in Lebanon, mental health disorders were not among the diagnoses found in their sample 17…”
Section: Discussioncontrasting
confidence: 84%
“…In 2009/2010 patients tended to present to the ED for diabetes mellitus, leukemia, and atherosclerosis, whereas in 2018/2019 infectious related diseases predominated such as pneumonia, bronchitis, and influenza. Even though reports from LMIC reported double burden of diseases in the ED, [11] our study showed that ED diagnoses are shifting from NCD towards CD. In comparison to other Middle Eastern and North African countries many NCDs, including cardiovascular diseases, chronic respiratory diseases, digestive diseases, have been mitigated except for diabetes and kidney diseases.…”
Section: Discussioncontrasting
confidence: 68%
“…The absence of those factors negatively affects policymaking, patient care, training programs, and resources allocation. [10,11] Previous studies in LMIC showed a double burden of diseases in the ED setting, including both non-communicable disease (NCD) and communicable diseases (CD). This was further studied in the ED setting at the largest hospital in Lebanon and the results confirmed that patients suffered from the double burden of NCDs and CDs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations